Definitive chemoradiation in patients with inoperable oesophageal carcinoma. - Crosby, T; Brewster, A; Borley, A; Perschky, L; Kehagioglou, P; Court, J; Maughan, T (2004)
We performed a retrospective study of 90 consecutive cases with inoperable carcinoma of the oesophagus treated with definitive chemoradiation at a single cancer centre between 1995 and 2002. For the last 4 years, 73 patients have received therapy according to an agreed protocol. This outpatient-based regimen involves four cycles of chemotherapy, cycles 3 and 4 given concurrently with 50 Gy external beam radiotherapy (XRT) delivered in 25 fractions over 5 weeks. Cisplatin 60 mg m(-2) day(-1) is given every 3 weeks together with continuous infusional 5-fluorouracil 300 mg m(-2) day(-1), reduced to 225 mg m(-2) day(-1) during the XRT. In all, 45 (50%) patients suffered one or more WHO grade 3/4 toxicity, grade 3 in 93% cases. Patients received more than 90% of the planned chemoradiation schedule. The median overall survival was 26 (15, >96) months, 51% (41, 64) and 26% (13, 52) surviving 2 and 5 years, respectively. Advanced stage, particularly T4 disease, was associated with a worse prognosis. Patients considered not suitable for surgery for reasons other than their disease, mainly co-morbidity, had a significantly better outcome, median survival 40 (26, >96) months, 2- and 5-year survivals 67% (54, 84) and 32% (13, 79), respectively (P<0.001). This schedule is a feasible, tolerable and effective treatment for patients with oesophageal cancer considered unsuitable for surgery.